Analisis Yuridis Terhadap Faktor-Faktor Penyebab Terbitnya Sertifikat Ganda Berdasarkan Putusan Nomor 21/PDT.G/2021/PN LBJ Di Kelurahan Labuan Bajo, Kecamatan Komodo, Kabupaten Manggarai Barat - Jemadut, Benedikta Renaastuti; Jacob, Yossie M Y; Pello, Helsina F (Artemis Law Journal, 2025)
Land with many benefits often causes problems or disputes, this is inseparable from the existence of regulations governing land ownership and utilization and the things above it. This research is a normative research, focusing on the analysis of legislation and related legal concepts. The method used in this research is literature study, the sources of legal materials used are primary, secondary, and tertiary laws. The method used to analyze the data is descriptive analysis. The results of the study show that the factors causing the issuance of duplicate certificates based on decision number 21 Pdt.G 2021 PN Lbj are the BPN which did not make changes to changes in land data to match conditions in the field, PPAT who was not careful in digging up information related to the object of sale and purchase including not being careful in understanding the subject's ability in sale and purchase, The related parties who deliberately distorted the facts as if the land transferred to him or the sale and purchase in 1989 never happened or happened but was invalid. The judge's consideration in deciding the dispute is to declare the lawsuit inadmissible (niet ontvankekijke verklaard) because the lawsuit is vague (obscuur libel).